Multivariable Flood Frequency Analysis of the Yujiang River Based on Annual Maximum Method and Peaks Over Threshold Method - CHEN Quanfu; LI Xungui (Renmin Zhujiang)
In recent years, significant changes in hydrological and engineering conditions have been observed in the Yujiang River basin, and climate anomalies have increased flood control pressures. The distribution of rainstorms and floods within the basin varies significantly, which makes it insufficient to describe flood risk solely from the perspective of flood peak or flood volume, and further study is necessitated. This paper takes the runoff data (1947–2015) from the Guigang Station as the research object and extracts flood sequences through the annual maximum (AM) method and the peaks over threshold (POT) method. Three common Archimedean Copula functions are employed to establish the multivariate joint distribution of flood variables, and their joint return periods and co-occurrence return periods are compared and analyzed. Results show that the optimal marginal distributions respectively obtained through the AM method and the POT method differ, with Clayton Copula being the optimal fitting function for the AM method and Frank Copula for the POT method. While the joint and co-occurrence return periods calculated through both methods show little difference, under the same return period, the POT method yields more reliable results for flood peak and flood volume. The findings can provide a valuable reference for decision-making in aspects of flood mitigation, engineering construction, and management in the Yujiang River basin.